Galanterie dziecięce. Spis zabawek z osiemnastowiecznego magnackiego inwentarza majątkowego - Penkała-Jastrzębska, Anna (Biuletyn Historii Wychowania, 2023)
A preserved register of items is an interesting and valuable source for research into everyday life of the 18th century nobility. The mentioned toys helped children to imitate everyday life activities as accurately as possible. Despite the fact that the items are a part of the magnate’s inventory, many of them showed signs of wear and tear while some were completely destroyed. The toys were often used but no particular attention was paid to regular repairs thereof. In the preserved source materials, we can easily find items for boys like military-related toys and play-horse heads on sticks. The typically girlish items included mostly dolls, dressed in costumes following the latest fashion. An interesting collection of toys consists of items that imitated various genre scenes, the nature of which may indicate the origin of the items. They created a miniature world, corresponding to the activities observed in everyday life. Unfortunately, the laconic nature of many entries in the register does not allow for more extended research based on the specific features of the items on the list. The problem of the representation of toys in the world of noble things requires an in-depth study of the preserved source materials, in order to recognize the specificity of this type of objects.